Snakes! - Stewart, Melissa (Washington, D.C. : National Geographic Society, 2009)
An introduction to the types, physical features, behavior, and pet potential of snakes.
It's a snake! -- Snakes all around -- Snakes and more snakes -- On the move -- Super snakes -- Snake senses -- Where's the snake? -- There's the snake! -- Snake snacks -- Snake pets -- Picture glossary.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Description based on print version record.
Keywords: Snakes -- Juvenile literature; Snakes; Electronic books- OSLIS; Electronic books